-6a-8a=6(-5a-2)-7(6-a)

Simple and best practice solution for -6a-8a=6(-5a-2)-7(6-a) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6a-8a=6(-5a-2)-7(6-a) equation:


Simplifying
-6a + -8a = 6(-5a + -2) + -7(6 + -1a)

Combine like terms: -6a + -8a = -14a
-14a = 6(-5a + -2) + -7(6 + -1a)

Reorder the terms:
-14a = 6(-2 + -5a) + -7(6 + -1a)
-14a = (-2 * 6 + -5a * 6) + -7(6 + -1a)
-14a = (-12 + -30a) + -7(6 + -1a)
-14a = -12 + -30a + (6 * -7 + -1a * -7)
-14a = -12 + -30a + (-42 + 7a)

Reorder the terms:
-14a = -12 + -42 + -30a + 7a

Combine like terms: -12 + -42 = -54
-14a = -54 + -30a + 7a

Combine like terms: -30a + 7a = -23a
-14a = -54 + -23a

Solving
-14a = -54 + -23a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '23a' to each side of the equation.
-14a + 23a = -54 + -23a + 23a

Combine like terms: -14a + 23a = 9a
9a = -54 + -23a + 23a

Combine like terms: -23a + 23a = 0
9a = -54 + 0
9a = -54

Divide each side by '9'.
a = -6

Simplifying
a = -6

See similar equations:

| -10+x=-3x+6 | | 2c+10=14 | | 4x+5=3+2x | | 6(w-3)=12 | | -22=n-19 | | -3k+k-2k=7k+66 | | 4+7=22 | | -3-x=5x+9 | | 3x^2-2x-4=0 | | -3-x=5x+93 | | 3x+45=24x | | (-5a+6)=2(3a+8) | | 7w+18+2w=w-6 | | 11-15=10-14 | | -5-2x=7+x | | -2m+5-m=2m-25 | | -25=-17-v | | 3+3i+8-2i-7= | | 4x+9y=72 | | .79+b=11.85 | | 66-3t=2t-84 | | n-7=3n-5 | | 5-2(x+3)=4x-19 | | 27+4n=6(n+2)+3 | | -x-12=4x+9 | | 2+9n=74 | | 25.30+f=227.70 | | x+38=4x-1 | | -2(2b+2)+(5b-2)=0 | | 60=3v-5v | | 5x-10=x+12 | | -96=4x+6x+4 |

Equations solver categories